The lower Niger and its tribes - Leonard, Arthur Glyn (Macmillan and co., limited; [etc., etc.], 1906)
Preface [by A.C.Haddon]--Introduction.--A geographical and traditional outline.--The philosophy of the people as expressed in words, names, proverbs, and fables.--The natural religion of the various tribes.--The naturism of the Delta.--The dualism of the natives.--Spirit land and spiritualism.--The spiritualism of the physical.--Embelmism, or The embodiment of the spirit.--The ceremonials and practices of naturism.--The demonology of the people as practised in witchcraft.--Appendices: A. A glimpse into the grammatical construction of the various tongues. B. The primitive philosophy of words. C. The further mentality and te deeper humanity of names.